Methanol Extract of Melastoma malabathricum Leaves as Eco-Friendly Corrosion Inhibitor for Mild Steel in Sulfuric Acid - Gusti, Diah Riski; Lestari, Intan; Farid, Faizar; Wahyudi, Abdi; Azril; Sukor, Mohd Zaki (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Methanol extract of Melastoma malabathricum (MEMML) contains secondary metabolites such as phenolics and flavonoids. These compounds have OH groups that can interact with Fe contained in steel and form a thin layer for corrosion inhibition on mild steel. Inhibition of mild steel corrosion using MEMML leaves in sulfuric acid solution was carried out using weight loss and potentiodynamic polarization methods. The results showed that the mild steel corrosion rate decreased and inhibition efficiency increased with the addition of MEMML. FTIR and SEM analysis showed the interaction between mild steel with MEMML forming a layer on the surface of the steel so that it inhibits corrosion. The inhibition efficiency has increased with the length of immersion time and concentration of MML methanol extract. The highest inhibition efficiency, 98.86%, was obtained at 72 hours of immersion time and 10 g / L MEMML.